Bosnia and Herzegovina between International Interventions and Dissolution - Vranješ, Aleksandar; Budimir, Željko (Napredak, 2023)
The state building process of Bosnia and Herzegovina beyond the provisions of the Dayton Peace Agreement has been implemented by the West for twenty-eight years through different forms. The goals which they failed to achieve in Dayton, they have tried to achieve by force, punishments, over-voting by foreign judges, impositions by high representatives, and by transferring the competences from the entities to a state level and suspending democracy. Their goal was to dismantle the Dayton Agreement and strengthen the state level government at the cost of the entity’s autonomy, but instead of unitarization, they turned B&H into a weak protectorate. Today, Bosnia and Herzegovina has a huge discrepancy between the Dayton constitutional system and the situation on the ground caused by decades of various foreign interventions in its political and legal system. The lack of potential solutions for getting out of the objectively dysfunctional state further strengthened the impression that B&H is moving in the direction of dissolution. The main focus of this paper is the claim that the interventions undertaken by one part of the international community in B&H have increased the potential of the dissolution of Bosnia and Herzegovina.